Hubungan Pengetahuan dan Sikap Ibu Hamil TM II dan TM III Terhadap Pemberian Pendidikan Sejak Dalam Kandungan - Nadya, Embun Nadya, Susilawati, Siti Khotimah (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2024)
Prenatal education can be understood as a conscious effort by parents (husband and wife) to educate their unborn child. The fetus can respond to stimuli from outside the womb, such as sound and music, which can affect their brain development and sensory skills. Various studies have proven the benefits of providing stimulation, including better adaptability and increasing intelligence potential. The purpose of this study was to determine whether there was a relationship between the mother's knowledge and attitude towards providing stimulation or prenatal education. The research method used was quantitative descriptive analytical design. The population of all pregnant women in TM II and TM III were 31 respondents who attended the routine monthly class for pregnant women at the Rizki Bangko Bdn Practice. The results of the study showed that the majority of pregnant women had routinely provided prenatal education, namely 61.3%, but there were still mothers who did not do prenatal education (12.9%) and there was a relationship between the level of knowledge and attitude of mothers and the provision of prenatal education with a P Value <0.05. Conclusion High knowledge and positive attitudes of mothers are the reference or awareness of mothers in providing prenatal education, on average, respondents have routinely attended Pregnant Women's classes, which is one of the bases for high knowledge and positive attitudes of mothers towards awareness of providing prenatal education.